If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 16y + -1 + 4y + 59 + -2y = 0 Reorder the terms: 4 + -1 + 59 + 16y + 4y + -2y = 0 Combine like terms: 4 + -1 = 3 3 + 59 + 16y + 4y + -2y = 0 Combine like terms: 3 + 59 = 62 62 + 16y + 4y + -2y = 0 Combine like terms: 16y + 4y = 20y 62 + 20y + -2y = 0 Combine like terms: 20y + -2y = 18y 62 + 18y = 0 Solving 62 + 18y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-62' to each side of the equation. 62 + -62 + 18y = 0 + -62 Combine like terms: 62 + -62 = 0 0 + 18y = 0 + -62 18y = 0 + -62 Combine like terms: 0 + -62 = -62 18y = -62 Divide each side by '18'. y = -3.444444444 Simplifying y = -3.444444444
| -5x^2-24x+5=0 | | 3x+6y=13 | | 6c-2(3c)=0 | | 2n^2-5n-4=6 | | 6b^2c+24bc+24c=0 | | 6*c-23c=0 | | x^2-6x-14=0 | | (b+12)(b-12)=0 | | g^2+9g=136 | | (B-12)(b+12)=0 | | (-7)+(-3)= | | 6*x-4=56+6 | | 12=b+9 | | x^2+18+32=0 | | x^2+x-28=0 | | ac-2bc=0 | | 15m+2=0 | | 9x^2-24xy+16y^2=0 | | g^2+7g=288 | | -3k-4=-2k+1 | | 12x^2-23+10=0 | | .5*p*8+b=84 | | .8/1.2=2/3 | | x-4x-2=-9x+4 | | 5d+7+4d-2d-6= | | 6x^2+4=5x | | 3x-x-7=2x+5 | | 8c+2c=-70 | | 2x^3+24x^2+54x=0 | | 2x-3=7x+3-4x | | -8y+4=-36 | | d+3d-10=0 |